2014
DOI: 10.1111/resp.12323
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial inflammation in hypersensitivity pneumonitis after antigen‐specific inhalation challenge

Abstract: This study shows that bronchial inflammation is present in patients with HP evidenced by increases in sputum neutrophils and eosinophils following exposure to the offending antigen during SIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A study on farmer's lung, another type of HP, revealed that large numbers of lymphocytes and high levels of IL-2 are present in the bronchoalveolar lavage fluid of people exposed to allergens, which might result in lymphocyte accumulation in the lung. Moreover, serum soluble IL-2 receptor was found to be expressed at a high level [17], and PF and Th2 dominance were observed when the disease evolved to the chronic stage; IL-4 was also produced by Th2 cells at a higher level [8]. In our previous study, Th1-associated cytokines were found to be highly expressed in PBL patients.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…A study on farmer's lung, another type of HP, revealed that large numbers of lymphocytes and high levels of IL-2 are present in the bronchoalveolar lavage fluid of people exposed to allergens, which might result in lymphocyte accumulation in the lung. Moreover, serum soluble IL-2 receptor was found to be expressed at a high level [17], and PF and Th2 dominance were observed when the disease evolved to the chronic stage; IL-4 was also produced by Th2 cells at a higher level [8]. In our previous study, Th1-associated cytokines were found to be highly expressed in PBL patients.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Although the presence of lymphocytic inflammation in the alveoli is characteristic in HP, in the bronchi it has been shown that there may be neutrophilic inflammation, especially in cases in which molds are the causative agent [ 12 , 14 ]. Our group has also recently confirmed that individuals with HP present significantly increased levels of neutrophils in induced sputum following the challenge with fungal agents [ 14 ]; this may explain the decrease in pH found in the present study after the challenge test in patients with HP caused by molds. Taken together, these findings also allow us to hypothesize that the mechanism of action of the HP may differ depending on the causative agent.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies using induced sputum have reported an increase in the total cell count and the lymphocyte count in patients with HP compared to the healthy population [ 11 – 13 ]. Also using induced sputum, our group recently demonstrated that bronchial inflammation is present in patients with HP, and is mainly evidenced by increases in neutrophils that worsen following exposure to the offending antigen during SIC [ 14 ]. However, other non-invasive methods for studying pulmonary inflammation have not been analyzed to date in patients with this disease.…”
Section: Introductionmentioning
confidence: 99%
“…In hypersensitivity pneumonitis, Villar et al . established that specific allergen challenge leads to measurable changes in inflammatory cells and protein markers in induced sputum . Overall, these studies point at the potential for utilizing novel serum and lung specific measures of disease activity to provide better understanding of disease behaviour and improved targeting of therapy.…”
Section: Rare Lung Diseasementioning
confidence: 95%